Principles of using English songs in teaching English to first year students at Ho Chi Minh University of industry - Vũ, Thị Hồng Vân (University of Languages and International Studies, 2017)
Chapter 1 is about the theoretical background related to the purpose of the study. Chapter 2 deals with investigating the situation of using English songs in teaching at HUI and finding out the principles of using songs to teach English for first year students at Ho Chi Minh University of Industry. Chapter 3 is concerned with applying the proposed principles of using songs in teaching English at HUI and then evaluating the feasibility of these principles when applied in real teaching at HUI.